Short-term association of NO2 with hospital visits for chronic kidney disease and effect modification by temperature in Hefei, China: A time series study - Jun Wu (Ecotoxicology and Environmental Safety, 2022)
Background: A large body of evidence has linked air pollution and temperature with chronic kidney disease (CKD) prevalence and hospitalizations. However, most studies have focused on the influence of heat stress on CKD prevalence, and the potential effect modification of temperature on the association between air pollution and CKD has not been well-investigated. In this study, we examined the associations of the whole temperature spectrum and air pollution with CKD-related hospital visits and explored whether temperature modifies the short-term association of air pollution with CKD-related hospital visits. Methods and findings: We collected 40 276 CKD-related hospital visits from the first Affiliated Hospital of Anhui Medical University and Anhui Provincial Hospital in Hefei, China, during 2015–2019. A two-stage time-series design was conducted to investigate the associations of air pollution and daily mean temperature with CKD-related hospital visits. First, we estimated the associations between air pollution and CKD-related hospital visits as well as temperature and CKD-related hospital visits. Second, we analyzed the associations of air pollution with CKD hospital visits at different temperatures. We found that NO2 exposure and low temperature were associated with an increased risk of CKD-related hospital visits. Low temperature enhanced the association between NO2 exposure and CKD-related hospital visits, with an increase of 4.30% (95% CI: 2.47–5.92%) per 10 μg/m3 increment in NO2 at low temperature. Effect modification of the association between NO2 and the risk of CKD-related hospital visits was stronger at low temperature across the whole population. Conclusions: Our findings indicate that low temperature–related chronic kidney damage should be of immediate public health concern. Impact of NO2 exposure on the risk of CKD–related hospital visits may increase under the low temperature, which suggests the need for NO2 exposure mitigation strategies in the context of climate change and an enhanced understanding of the mechanisms underlying the temperature variance of air pollution effect to help reduce the magnitude of the CKD burden on the healthcare systems.